Association of the cMIND diet with cognitive impairment in older adults: evidence from a 10-year nationwide study - Cai, Dahuan; Zeng, Yanxin; Xu, Xiaoping; Ye, Mengliang; Song, Anchao; Chen, Min (Frontiers in Nutrition, 2026)
BackgroundThe protective effects of the Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) diet against cognitive impairment have been well-established in European and North American populations. However, due to differences in dietary patterns, evidence from cohort studies on the association between the currently adapted MIND diet and cognitive impairment in Chinese older adults remains limited, and a causal relationship has yet to be determined.MethodsA total of 8326 Chinese Longitudinal Healthy Longevity Survey (CLHLS) participants were included in this study. The Chinese version of the Mediterranean-DASH intervention for neurodegenerative delay (cMIND) diet scores ranged from 0 to 12 based on validated food frequency questionnaire responses. A Cox proportional hazards model was used to assess associations between cMIND diet and cognitive impairment in older adults. Restricted cubic spline plots were used to assess the linear relationship between cMIND and cognitive impairment.ResultsThe study found a significant nonlinear relationship between cMIND diet and cognitive impairment (P-overall < 0.001, P-non-linearity = 0.021). Compared with elderly people on a low-level cMIND diet, olders people on a high-level diet had a lower risk of developing cognitive impairment (HR = 0.79, P < 0.001). Subgroup analysis indicated that a high-level cMIND diet provided stronger protective effects for males (HR = 0.75, P < 0.001), rural residents (HR = 0.72, P < 0.001), and younger elderly individuals (HR = 0.71, P = 0.004).ConclusionHigh adherence to the cMIND diet effectively reduces the risk of cognitive impairment in the Chinese elderly population, with enhanced protective effects observed specifically in males, those residing in rural areas, and younger elderly individuals.